Method of UV-Metric and pH-Metric Determination of Dissociation Constants of Ionizable Drugs: Valsartan - Meloun, Milan; Pilařová, Lucie; Pfeiferová, Aneta; Pekarek, Tomas (Springer, 2019)
Valsartan is used for treating high blood pressure, congestive heart failure and to increase the chances of living longer after a heart attack and to reduce the mortality rate for people with left ventricular dysfunction following a heart attack. Regression analysis of the pH-spectra with REACTLAB and of the pH-titration curve with ESAB determined two close consecutive dissociation constants. MARVIN and ACD/Percepta predicted two protonation sites. In water a soluble anion L2- forms two sparingly soluble species LH-, LH2. Although adjusted pH less affected the spectral changes in the chromophore, pK(a1)(T) = 3.70 +/- 0.12, pK(a2)(T) = 4.82 +/- 0.08 at 25 degrees C and pK(a1)(T) = 3.44 +/- 0.08, pK(a2)(T) = 4.67 +/- 0.02 at 37 degrees C in an aqueous phosphate buffer were determined. By regression analysis of potentiometric pH-titration curves and pK(a1)(T)= 3.51 +/- 0.01, pK(a2)(T) = 4.63 +/- 0.01, at 25 degrees C and pKT(a1) = 3.44 +/- 0.03, pK(a2)(T) = 4.51 +/- 0.03 at 37 degrees C in an aqueous medium were estimated. Positive enthalpy values Delta H-0(pK(a1)) = 10.33 kJ.mol(-1), Delta H-0(pK(a2)) = 17.70 kJ.mol(-1) showed that the dissociation process was endothermic. The standard state Gibbs energy changes are Delta G(0)(pK(a1)) = 20.03 kJ.mol(-1), Delta G(0)(pK(a2)) = 26.43 kJ.mol(-1) at 25 degrees C and the Delta S-0 at 25 degrees C and 37 degrees C are (Delta S-0(pK(a1)) = - 32.56 J.K-1.mol(-1), Delta S-0(pK(a2)) = - 29.26 J.K-1.mol(-1) at 25 degrees C and Delta S-0(pK(a1)) = - 30.01 J.K-1.mol(-1), Delta S-0(pK(a2)) = - 25.92 J.K-1.mol(-1) at 37 degrees C. [GRAPHICS] .
Metoda UV-metrického a pH-metrického stanovení disociačních konstant ionizovatelných léčiv: Valsartan
Keywords: Dissociation constants; Valsartan; Spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB; Dissociation constants; Valsartan; Spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB